Problemas de linguagem e de alimentação: manifestações da fixação oral na clínica fonoaudiológica - Bom, Roberta Bomfim Pedro (2012)
In the speech therapy clinical practice, the relation between the feeding and language disorders became object of researches due to the frequence with that these disorders co-occur in children. Actually, studies indicate the co-occurrence of feedind an language disorders as an orality problem. The purpose of this research was to investigate the nature of the manifestation of the co-occurrence between the feeding and language disorders, in the childhood, and the action of the parental desire and speech in the subject s constitution and your relation with the assumption of a self without body and psychic autonomy. To achieve it, the method was clinical-qualitative carried out by means of one clinical case study, Guilherme, four years. Joined to it, there was a bibliographic revision of the speech therapy and psychoanalytic literatures. Knowing of the relation between the theoretical and clinical material, I formulated the thesis of that the co-occurrence of feeding and language disorders can be understood like a fixation on the oral stage of the organization of the libido; promoted by the maternal desire of that nothing changes desire that denies the birth of a singular and autonomous subject. Thus, it can be concluded that the treatments that aim to adapt, of the dichotomous way, the oral functions can bring superficial results, without the guarantee of the understanding of the pathological manifestations. From the transference, concept of the Psychoanalysis, the speech therapy setting must allows the transit of the affects presents on the parental and children s speech, which, from my point of view, to permit better results on the therapeutic intervention